Hak Warga Negara Dalam Memperoleh Pendidikan - Emmanuel Sujatmoko (Jurnal Konstitusi, 2016)
The state are obliged to ensure a quality education and without discrimination to every citizen, to meet the educational rights of every citizen, in order to produce the output quality of education really qualified. Starting from the lofty goals for the nation’s intellectual life as stated in the opening of the Constitution of 1945, until now, the efforts to develop the intellectual life of the nation seems to still have a lot of obstacles. Increasing numbers of poor families in Indonesia since the economic crisis that hit in mid-1998 and more children are forced (or forced) to beg in    the streets and singing when they should be in classrooms to learn. The ignorance is a source of oppression for humanity, if up to this time, the state did not implement its obligations in fulfilling the rights of its citizens to acquire basic education, then the state has violated human rights and constitutional violations.